CYBER SECURITY EDUCATION PROGRAM FOR STUDENTS TO BUILD DIGITAL SECURITY AWARENESS - Agus Iskandar; Bagas Ade S (Adisam Publisher, 2024)
In the ever-evolving digital era, cyber security is a major concern, especially for the younger generation who spend significant time online. The Cyber Security Education Program for Students is designed to equip students with essential knowledge and skills in dealing with cyber security threats. Through a series of interactive workshops, training and simulations, this program aims to build awareness of the importance of digital security, teach how to identify and avoid various types of cyber attacks, and promote best practices in keeping personal and sensitive information safe. The program curriculum is structured based on the latest cybersecurity frameworks and delivered in a format that is easy for students to understand. The training material covers the basics of cyber security, such as password security, recognition of phishing, malware and ransomware, as well as self-defense techniques in cyberspace. In addition, this program also integrates the use of digital tools that can help students practice cybersecurity in their daily lives. By participating in this program, it is hoped that students will become more aware and responsible in exploring the digital world, and be able to protect themselves and others from potential cyber security dangers. The Cyber Security Education Program for Students not only emphasizes the importance of cyber security knowledge and skills, but also encourages students to become digital security ambassadors in their environment, thereby creating a safer and more informed digital society.